School leadership and indigenous student outcomes: A correlational study of Student Needs Management Practices based on Maslow’s Hierarchy of Needs - Yusoff Yahaya; Bity Salwana Alias; Mohd Norazmi Nordin (PLoS ONE, 2026)
Indigenous students continue to face persistent educational disadvantages, including lower academic attainment and reduced school engagement, often linked to school systems that do not systematically address students’ hierarchical needs. This study examined the association between principal-led Student Needs Management Practices (SNMP) and Indigenous student outcomes across 93 national primary schools in Orang Asli settlement areas in Peninsular Malaysia. Using a quantitative cross-sectional design, data were collected from 342 teachers through multi-stage sampling. SNMP was operationalised across five Maslow-derived dimensions physiological, safety, belongingness, esteem, and self-actualisation needs while Indigenous student outcomes encompassed academic achievement, co-curricular participation, and character development. Both SNMP (M = 4.63, SD = 0.39) and student outcomes (M = 4.26, SD = 0.49) were rated at very high levels by teacher respondents. Pearson correlation revealed a significant, moderate positive association between SNMP and student outcomes (r = .411, p < .001). Multiple regression indicated that the five SNMP dimensions collectively explained 18.8% of the variance in student outcomes (R 2 = .188, adjusted R 2 = .176), F(5, 336) = 15.559, p < .001. Belongingness needs emerged as the only statistically significant predictor (β = .298, p < .001); safety needs approached significance (β = .124, p = .061); physiological, esteem, and self-actualisation needs were not significant predictors. These findings suggest that emotional and relational dimensions of leadership practice are more directly associated with Indigenous student outcomes than material or recognition-based dimensions, and that the modest direct association is consistent with leadership-influence models in which principals affect student outcomes substantially through intermediate mechanisms such as teacher commitment. The study offers evidence-based implications for needs-responsive school leadership in Indigenous education contexts.